The influence of intestinal microbiota on the development of type 1 diabetes - Augustowska, Katarzyna; Protasiuk, Agnieszka; Sierzpowski, Rafał; Tymoszuk, Patrycja; Żak, Agata (Journal of Education, Health and Sport, 2024)
Introduction and purpose Type 1 diabetes (T1D) is an autoimmune disease that results in the destruction of pancreatic β cells, which leads to insulin deficiency and hyperglycemia. One significant factor that may influence the development of type 1 diabetes is a change in the intestinal microbiota. This study aim is to present the significance and role of intestinal microbiota in the pathogenesis of T1D. This subject is important, as it offers prospects for new therapeutic solutions, especially given the significant social impact of T1D. Description Type 1 diabetes (T1D) causes a number of symptoms and complications, including an increased risk of developing cardiovascular diseases. Diagnosis includes measurements of glucose concentration, glycated hemoglobin, and specific antibodies in the blood. The basic therapy for T1D is insulin replacement therapy. Numerous studies have shown that both the composition and function of the intestinal microbiota are impaired in patients with T1D. It has been observed that an increase in the number of Bacterioides and a decrease in the number of Firmicutes, which are the main microorganisms of the intestinal microbiome, are correlated with a high risk of developing T1D. Summary Type 1 Diabetes (T1D) is a serious health problem that affects many people worldwide and the incidence of the disease is constantly increasing. There is a growing number of studies that emphasize the influence of the intestinal microbiota on the development of T1D. It is important to enlarge our knowledge about this disease. Further studies are needed to determine the importance and the role of the intestinal microbiota in the pathogenesis of T1D.